Optimizing flow properties of the different nanofluids inside a circular tube by using entropy generation minimization approach - Mohseni-Gharyehsafa, Behnam; Ebrahimi-Moghadam, Amir; Okati, V.; Farzaneh-Gord, Mahmood; Ahmadi, Mohammad Hossein; Lorenzini, Giulio (Journal of thermal analysis and calorimetry, 2019)
The use of nanofluids as working fluid is one of the represented methods in efficiency enhancement of various systems. One of the most important subjects in nanofluid utilization is finding the optimal conditions. In this study, the efforts have been made to find optimal condition of forced convection nanofluid flow inside a circular tube. The flow is assumed turbulent, and optimization process is carried out for two metallic oxide nanoparticles (Al 2 O 3 , CuO) and one nonmetallic oxide nanoparticle (SiO 2 ), dispersed in a 60:40% ethylene glycol/water base fluid. The optimization process has been performed based on the second law of thermodynamic and entropy generation minimization approach. The process has been focused on finding the optimal values for volume fraction, Reynolds number, diameter of particles and average flow temperature. Results show that two metallic oxide nanofluids generate less entropy compared with nonmetallic oxide nanofluid. In addition, comparing these two metallic oxide nanofluids, the maximum amount of total entropy generation is 20% lower when CuO nanoparticles added to the base fluid instead of Al 2 O 3 .